Whole genome sequencing analysis and functional characterization of Lacticaseibacillus rhamnosus HP-B1083 - Da-Hu Zhang; Zhen-Dong Tian; Bao-Zhi Ge; Qian-Meng Qi; Jia-Lin Lv; Hang Wu; Shao-Yang Hou; Shu-Hang Zhang (Brazilian Journal of Microbiology, 2026)

Phylogenomics of Tanypodinae (Diptera: Chironomidae) redefines relationships in Procladiini and Tanypodini and supports a new tribe - Xiu-Ru Xiao; Yi-Ni Zhang; Hai-Feng Xu; Zhi-Chao Zhang; Yu-Yi Jiang; Yan-Xin Chen; Chen-Hong Li; Bing-Jiao Sun; Fabio Laurindo da Silva; Xiao-Long Lin (Molecular Phylogenetics and Evolution, 2026)

An enhanced YOLO-based deep learning framework for automated structural defect inspection in complex backgrounds - Zheyu Liu; Di Su; Youqi Zhang; Da-Wei Lin; Zhen Sun (Engineering Structures, 2026)

Methylene blue-functionalized blue/red dual-emissive carbon dots for ratiometric fluorescence detection of sunset yellow in food - Sihao Wang; Yifan Zhang; Dejin Lin; Jingqi Wang; Yihao Zhang; Siting Peng; Junyuan Shi; Siqi Xu; Da Chen (Analytica Chimica Acta, 2026)

Avermectin induces developmental toxicity and immunotoxicity in zebrafish larvae - Wei-Guo Wang; Shou-Lin Li; Da-Wei Yan; Yun-Fei Sha; Wen-Ping Xu; Jia-Gao Cheng; Zhong Li; Li-Ming Tao; Yang Zhang (Journal of Environmental Sciences, 2026)

Plastic-mediated alterations in soil microbial networks and their role in sulfamethazine degradation - Yuqiu Ye; Luoqin Shen; Da Lin; Tianlun Zhang; Yaning Wang; Lu Lu; Yifei Qin; Dong Zhu (Journal of Environmental Sciences, 2026)

Spatiotemporal radical engineering via non-destructive synchrotron lithography for multimodal functionalization of inert polymers - Hao Zhang; Xincheng Xie; Shengbin Cao; Fan Zhang; Lin Da; Yang Liu; Bomin Liu; Feng Tian; Caizhen Zhu; Xiuhong Li; Jian Xu (Chemical Engineering Journal, 2026)

Minutes-long soft X-ray prompt emission from a compact object merger - An Li; Chen-Wei Wang; Niccolò Passaleva; Jie An; Bin-Bin Zhang; Eleonora Troja; Yi-Han Iris Yin; Yuan Liu; Shao-Lin Xiong; Li-Ping Xin; Yi-Xuan Shao; Jun Yang; et al. (Science Bulletin, 2026)

Natural deep eutectic solvents assisted the encapsulation of curcumin in gellan gum hydrogels - Yu-Nan Pan; Jia-Cheng Liu; Lin-Da Zhang; Bin Lai; Ce Wang; Jia-Nan Yan; Hai-Tao Wu (Food Research International, 2026)

Atomically precise ferrocene-based Fe/Mn nanocluster for solar-driven cycloaddition of epoxides with carbon dioxide - Xue-Feng He; Chun-Yang Li; Yu-Lin Jiang; Wan-Yu Zhu; Qiu-Hong Cheng; Kun Huang; Da-Bin Qin; Xiang-Yu Zhang (Chemical Engineering Journal, 2026)

The undescribed alkaloids from Jacobaea cannabifolia (less.) E. Wiebe and their anti-inflammatory activities - Jian-Zhe Li; Juan Pan; Yu Bi; Zhi-Chao Hao; Wei Guan; Hai-Xue Kuang; Qing-Shan Chen; Li-Li Zhang; Xin-Yue Wu; Da-Lin Li; Bing-You Yang; Yan Liu (Natural Product Research, 2026)

Functional noncoding variants within the TBX1 enhancer contribute to tetralogy of Fallot - Jimiao Gao; Tao Jiang; Yingyi Quan; Xinyue Liu; Min Da; Jiang Jiang; Jun Zhou; Hao Sun; Yan Zhou; Wanting Ma; Zicheng Zhang; Yiwei Cheng; et al. (Science China Life Sciences, 2026)

Corrigendum to Avermectin induces developmental toxicity and immunotoxicity in zebrafish larvae. Journal of Environmental Sciences (2026), doi: https://doi.org/10.1016/j.jes.2026.03.02 - Wei-Guo Wang; Shou-Lin Li; Da-Wei Yan; Yun-Fei Sha; Wen-Ping Xu; Jia-Gao Cheng; Zhong Li; Li-Ming Tao; Yang Zhang (Journal of Environmental Sciences, 2026)

Copolymer hydrogel formed by κ-carrageenan and chickpea protein amyloid fibrils: From rheological properties to regulation of aggregation morphology - Lin-Da Zhang; Xiao-Lei Zang; Yu-Nan Pan; Jia-Cheng Liu; Jia-Nan Yan; Bin Lai; Ce Wang; Hai-Tao Wu (Food Hydrocolloids, 2026)

Ultrasound-driven structural and functional modifications of grape seed protein revealed by power- and duration-dependent experiments - Ying-Yang Liu; Da-Rui Tang; Shi-Ling Wang; Wei-Wei Li; Jun-Wei Xu; Lian-Bing Lin; Yu-Hang Jiang; Qi-Lin Zhang (Food Hydrocolloids, 2026)

In-situ thiosulfate pretreatment enhances anaerobic fermentation of biodegradable plastic wastes into short-chain fatty acids: Degradation performance, microbial synergy and metabolic pathway - Boyi Cheng; Da Zhang; Qingshan Lin; Jinqi Jiang; Wugui Zou; Feixiang Zan; Shuai Zhou; Zongping Wang; Guanghao Chen; Gang Guo (Bioresource Technology, 2026)

Simultaneous removal of organic and inorganic arsenic: A critical evaluation of direct adsorption and hybrid catalytic oxidation-adsorption pathways - Huiping Zeng; Guoyang Ma; Xiaoying Zheng; Da Lin; Jie Zhang; Dong Li (Chemical Engineering Journal, 2026)

Optimization of pediatric dosing regimens for aztreonam and amoxicillin/clavulanate combination therapy against multidrug-resistant bacteria - Lili Wang; Mengyuan Wu; Lin Qu; Pengfei Wang; Ziwei Yu; Hua Deng; Frederico S. Martins; Jiayuan Zhang; Da Rong; Mingming Yu; Zhihua Lv; Sherwin K. B. Sy; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

Study on prestack reservoir prediction of deep volcanic rock gas reservoirs in Chaganhua sub-sag of Songnan Fault Depression - Qin-lin Yang; Xue-pei Fan; Chen-chen Bi; Lan-mei Ke; Ye Yang; Da Zhang; Shu Wang (Applied Geophysics, 2026)

Aggregation caused quenching of dual-emission nitrogen-doped carbon dots for visual quantitative and ratiometric detection of pesticide residues - Xinyu Luo; Dejin Lin; Jingqi Wang; Yihao Zhang; Xinru Liu; Sineng Gao; Da Chen (Food Chemistry, 2026)

Comprehensive understanding of new particle formation in China through advanced modeling - Jiewen Shen; Bin Zhao; An Ning; Wei Nie; Chao Yan; Yuyang Li; Runlong Cai; Alfonso Saiz-Lopez; Manish Shrivastava; Biwu Chu; Da Gao; Nanna Myllys; et al. (Science Bulletin, 2026)

Gene Regulatory Networks Controlling Fruit Anthocyanin Accumulation: A Review - Da Zhang; Bowei Zhu; Xin Liu; Han Wang; Guodong Zhao; Lin’guang Jia; Dongmei Chen; Tongsheng Zhao; Gang Niu; Chaohong Zhang; Xinsheng Zhang (Applied Fruit Science, 2026)

Integrated basin-scale assessment of legacy and emerging PFAS in the Xiangjiang River Basin, China: Occurrence, source apportionment, and risk prioritization - Da-Ying Lin; Li-Xin Hu; You-Sheng Liu; Jin-Na Zhang; Guang-Guo Ying (Water Research, 2026)

In-situ reactivation of the catalyst for hydrodeoxygenation of bio-oil to biofuel by coupling the self-rotation and revolution of catalysts in the swirling flow - Yao Zhang; Zheng-hao Yang; Yu-long Chang; Jian-ping Li; Bang-da Wang; Zi-heng Jin; Liang Ma; Xia Jiang; Hua-lin Wang (Journal of Cleaner Production, 2026)

Improvement of indoor air quality and health effects in COPD patients in a heavy industrial area - Jia Lin Zhang; Yi Ting Chang; Ching Yu Hsiao; Chung-Shin Yuan; Yen-Ping Peng; Da Wei Wu; Huang-Chi Chen; Jia-Yu Kuo; Huai-Lei Juan; Pei-Shih Chen (Environmental Research, 2026)

A novel endophytic Kineococcus from rice against Fusarium culmorum and Fusarium sporotrichioides and whole-genome analysis - Yayun Liu; Lin Liu; Zhuanxia Lei; Ruping Zhang; Lin Zhao; Fenglan Li; Da Zhang; Qingyue Yu (Antonie van Leeuwenhoek, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Chitosan-SNAP composite coating with sustained NO release for microbial killing and tomato preservation - Jie Chen; Hui Zhang; Yuxin Lin; Jinyu Liu; Yisong Chen; Xiaoyan Zhang; Hetong Lin; Da-Peng Yang (Food Chemistry, 2026)

EED226 treatment targets key immune genes to suppress LPS response in Chinese tongue sole splenocytes - Yangqing Zhang; Lei Lin; Duan Liao; Shengyu Zhu; Yanan Li; Lucas Benites Doretto; Ivana Felipe da Rosa; Yajun Wang; Hong-Yan Wang; Changwei Shao (Fish & Shellfish Immunology, 2026)

Enhancing capacitive energy storage in Na0.5Bi0.5TiO3-based relaxor ferroelectric ceramics by tuning polymorphic polar nanoregions - Binglong Zheng; Ying Lin; Fei Yan; Qibin Yuan; Yongzhen Ma; Yanlong Ma; Yu Zhang; Da Li; Haibo Yang (Chemical Engineering Journal, 2026)

Screening and In Vivo Validation of Key Genes Involved in Myelin Damage in Alzheimer’s Disease - Hai-Tao Li; Ji-Wei Zhang; Bo-Wen Li; Hong-Yun Wu; Jin-Wen Ge; Da-Hua Wu; Quan-Lin Zhao; Ya-Han Wang (Molecular Neurobiology, 2026)

The inhibitory mechanisms of plasma-activated water on biofilm formation of Pseudomonas fluorescens by disrupting quorum sensing - Yi-Ming Zhao; Lin Zhang; Yulong Bao; Yiting Guo; Haile Ma; Ronghai He; Paula Bourke; Da-Wen Sun (Food Research International, 2025)

Neutrophil extracellular trap (NET)-targeted nanoparticles alleviate myocardial ischemia–reperfusion injury in mice by inhibiting macrophage–myofibroblast transition - Da Lu; Wei Jiang; Xi Zhang; Jiangshui Liang; Meng Xiong; Changzhi Yan; Anyi Lin; Teng Ma; Feng Zhu; Yongqiang Dong (Chemical Engineering Journal, 2025)

Microplastics modulate neutrophil migration via an ROShistone lactylation positive feedback loop - Yi-li Wang; Xiao-chen Yuan; Chun-jiao Wei; Ke-yun Li; Lin-xi Zuo; Hao-yi Zhang; Rui-chen Ding; Ren Zhou; Yun-hua Zhang; Da-long Ren (Journal of Hazardous Materials, 2025)

Separation and recovery of vanadium from leaching solution of calcium roasting vanadium slag by extraction with P204 extractant - Da-long Wang; Lin Zhang; Jing-wei Li; Chen Chen; Yin-he Lin; Zhi Yang; Da-ya Wang; Huan-jian Hou; Jian Chen; Tang-jie Zhou; Wen-ming Tang (Minerals Engineering, 2025)

System characteristics of integrated continuous flow simultaneous partial Nitrification, Anammox and Denitrification (SNAD) for NH4+-rich wastewater: performance, sludge evolution, metagenomic sequencing analysis - Peng-fei Yu; Ding Wang; Xing-guan Ma; Yu-bo Fu; Li-yao Han; Ao Wang; Dian-lin Jiang; Hai-wen Sun; Dong-xue Li; Xing Jin; Kang-da Yang; Li-cheng Zhang; et al. (Environmental Research, 2025)

Vanadium-cobalt oxide nanoflower catalyst for efficient and stable overall water splitting in alkaline and seawater electrolytes - Yong-qi Tian; Song-lin Xu; Jia Li; Shuang-shuang Zhang; Bo-yao Zhang; Rong-da Zhao; Fu-fa Wu; De-peng Zhao (Next Research, 2025)

Synthesis of magnetic zeolite from iron sludge and fly ash for simultaneous nitrogen and phosphorus removal - Huiping Zeng; Simin Li; Jiongru Liang; Zhanguo Li; Da Lin; Jie Zhang; Dong Li (Journal of Water Process Engineering, 2025)

Metabolomic profiling unveils biochemical dynamics in spontaneously fermented grape leaf by-products: towards sustainable agricultural waste valorization - Jia-Lin Xing; Yun-Lu Song; Yan-Ge Li; Lu Yang; Ke-Ying Duan; Ding-Ding Zuo; Jing Zhang; Hai-Nan Liu; Tong-Lu Wei; Mao-Song Pei; Da-Long Guo (Food Bioscience, 2025)

Glutaminolysis and α-ketoglutarate-stimulated KCa3.1 expression contribute to β-adrenoceptor activation-induced myocardial fibrosis in mice - Ru-Yue Bai; Lin-Hong Wu; Yan Wang; Chen Guo; Gang She; Zheng-Da Pang; Jing-Jing Li; Xin-Yi Zhao; Meng-Zhuan Han; Xia-Xia Hai; Yi-Yi Yang; Yi Zhang; et al. (Science China Life Sciences, 2025)

Land-use types impact soil ecosystem functions by altering the soil multitrophic biodiversity and interactions - Tian-Lun Zhang; Shao-Yang Zhang; Lu Wang; Da Lin; Bang Ni; Tian-Gui Cai; Shuai Du; Dong Zhu (Soil Ecology Letters, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Insights into the mechanism of ameliorative antioxidant activity and hydration characteristics in cold plasma-induced glycosylated peanut protein products - Jiao-jiao Yu; Ran-ran Zhang; Da-Qiao Yang; Xiang-na Lin; Wen-jie Fu; Yi-qi Shao; Hui Ji; Zhan-yong Guo (Food Chemistry, 2025)

Photocatalytic H2 fumigation technology enhanced FSG/CS nanocomposite films for banana packaging - Jie Chen; Kaiwei Huang; Xiaoyan Zhang; Hetong Lin; Da-Peng Yang (Chemical Engineering Journal, 2025)

A new strategy of fruit preservation: Photoinduced hydrogen evolution technology combined with fish scale gelatin/chitosan-based bio-nanocomposite film - Jie Chen; Xiaoyan Zhang; Hetong Lin; Gang Chen; Wanli Zhang; Da-Peng Yang (Chemical Engineering Journal, 2025)

Boosting catalytic performance of N doped porous carbon derived from coal tar pitch: The role of N species and the contribution of 1O2 - Linlin Huang; Xuwen Zhang; Lin Wang; Tingting Liu; Da Li; Tao Sheng; Caiyu Sun; Lixin Li (Journal of Water Process Engineering, 2025)

Association between sleep quality and serum biomarkers among long-term hot spring bathers: a cross-sectional study - Fen Yang; Yue Zou; Ying-ying Zhang; Hong-xia Li; Yi-hang Xu; Bao-chao Zhang; Lin-xuan Liao; Meng-xi Cao; Rui-xue Wang; Yuan Yuan; Yun Zhou; Da-yong Zeng; et al. (International Journal of Biometeorology, 2025)

Gelation melioration of clam Meretrix meretrix surimi based on the interactions with different plant/animal proteins - Lin-Da Zhang; Yue Liu; Ying-Rui Wang; Tian-Qi Zhou; Jia-Cheng Liu; Jia-Nan Yan; Bin Lai; Ce Wang; Hai-Tao Wu (Food Chemistry, 2025)

Metaproteomics reveals metabolic activities potentially involved in bloom formation and succession during a mixed dinoflagellate bloom of Prorocentrum obtusidens and Karenia mikimotoi - Hua-Min Cheng; Xiao-Lian Ning; Shu-Feng Zhang; Hao Zhang; Lin Lin; Si-Qi Liu; Da-Zhi Wang (Science of The Total Environment, 2025)

Gelation improvement of low-salt Chinese shrimp (Fenneropenaeus chinensis) surimi gel by L-arginine - Yue Liu; Lin-Da Zhang; Ying-Rui Wang; Tian-Qi Zhou; Yu-Qiao Wang; Jia-Nan Yan; Bin Lai; Ce Wang; Hai-Tao Wu (Food Chemistry, 2025)

Gelation properties and swallowing characteristics of heat-induced whey protein isolate/chia seed gum composite gels as dysphagia food - Lin Li; Yu-Qiao Wang; Lin-Da Zhang; Jia-Nan Yan; Ce Wang; Bin Lai; Hai-Tao Wu (Food Chemistry, 2025)

Enhancing indoor air quality and cardiopulmonary health in patients with asthma by photocatalytic oxidation and filters air cleaner - Jia Lin Zhang; Guan-Yu Liao; Hong-Yi Lin; Jie-An Xie; Wan-Chen Li; Huang-Chi Chen; Da Wei Wu; Huai-Lei Juan; Jia-Yu Kuo; Pei-Shih Chen (Journal of Hazardous Materials, 2025)

Metal/organic interface carrier quenching suppression for stable and efficient near-infrared quantum dot light-emitting diodes - Wan-Shan Shen; Yang Liu; Xingtong Chen; Hong-Wei Duan; Jia-Lin Pan; Zhong-Da Zhang; Feng Zhao; Zeke Liu; Sui-Dong Wang; Wanli Ma; Song Chen; Ya-Kun Wang; et al. (Chemical Engineering Journal, 2025)

On the multiscale processes leading to three heavy rainfall episodes over beijing and its periphery in july 2016 - Rudi Xia; Chong Wu; Da-Lin Zhang; Yali Luo; Jinfang Yin (Meteorology and Atmospheric Physics, 2025)

Comparative analysis of size-fractional eukaryotic microbes in subtropical riverine systems inferred from 18S rRNA gene V4 and V9 regions - Guanglong Zhang; Zhenli Guo; Yue Ke; Hanyi Li; Xilin Xiao; Da Lin; Lujian Lin; Yanhong Wang; Jingchun Liu; Haoliang Lu; Hualong Hong; Chongling Yan (Science of The Total Environment, 2024)

Shining light on broad-spectrum responded NaYF4:Yb,Er,Tm@Bi@BiOI: Understanding the enhanced photodegradation performance of bisphenol A and mechanisms - Jinyuan Zhang; Tian Shi; Qincan Ma; Shuang Fu; Da Cai; Fuhua Gao; Xianzhong Lin; Yueli Zhang (Journal of Environmental Management, 2024)

Mechanism of discoloration of Antarctic krill oil upon storage: A study based on model systems - Xiang-Bo Zeng; Xue-Chen Pei; De-Yang Li; Fa-Wen Yin; Hui-Lin Liu; Meng-Ling Jin; Jiang-Hua Zhang; Da-Yong Zhou (Food Chemistry, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Petrogenesis of the pyroxenitic Moho transition zone in the Zedong ophiolite, Southeastern Tibet - Zhen-Yu Zhang; Chuan-Zhou Liu; Yan Liang; Liang-Liang Zhang; Chang Zhang; Tong Liu; Bo-Da Liu; Wei-Qi Zhang; Yin-Zheng Lin; Wen-Bin Ji (Lithos, 2024)

Impact of plant and animal proteins with transglutaminase on the gelation properties of clam Meretrix meretrix surimi - Lin-Da Zhang; Lin Li; Qian Zhang; Yu-Qiao Wang; Yue Liu; Jia-Nan Yan; Bin Lai; Ce Wang; Hai-Tao Wu (Food Bioscience, 2024)

Integrating L-cysteine coated polydopamine nanoparticles and deep eutectic solvents into chitosan matrix for multifunctional food packaging application - Ying Mao; Malin Cui; Xiaoyan Zhang; Hetong Lin; Da-Peng Yang (Chemical Engineering Journal, 2024)

Regulating iron center by defective MoS2 for superior Fenton-like catalysis in water purification: The key role of surface interaction and superoxide radical in accelerating metal redox-cycling - Ai-Yong Zhang; Zhi-Xian Lin; Jing-Yu Zhang; Ming-He Zhang; Chi Zhang; Lu Zhao; Liang Liu; Wei Da; Lyumeng Ye (Chemosphere, 2024)

Refining metallic nano-copper by electron-rich black carbon for superior Fenton-like catalysis in water purification: The capacitive regulation of corrosive electron transfer - Lu Zhao; Xing-Bo Chen; Xin-Ru Hu; Lei Chen; Shun Feng; Ai-Yong Zhang; Shu-Chuan Peng; Zhi-Xian Lin; Chu Jiang; Wei Da; Qi-Xin Wei (Journal of Hazardous Materials, 2024)

Upregulation of hsa-miR-141-3p promotes uterine cervical carcinoma progression via targeting dual-specificity protein phosphatase 1 - Zi-Qian Liang; Wei Zhang; Da-Tong Zeng; Jun-Hong Chen; Jia-Yuan Luo; Lin Shi; Kang-Lai Wei; Gang Chen (Functional & Integrative Genomics, 2024)

Regulation of gene expression in the secondary metabolic synthesis pathway of Lonicera japonica Flos by yeast polysaccharides - Xu-peng Gu; Lin-lin Yang; Da-ming Qi; Di Zhang; Tian-liang Liu; Cheng-ming Dong (Physiology and Molecular Biology of Plants, 2024)

An improved representative of stomatal models for predicting diurnal stomatal conductance at low irradiance and vapor pressure deficit in tropical rainforest trees - Wei Xue; Xue-min He; Quan Wang; Pei-jun Shi; Guang-hui Lv; Jian-feng Huang; Da Yang; Jiao-lin Zhang (Agricultural and Forest Meteorology, 2024)

PLD2 deletion ameliorates sepsis-induced cardiomyopathy by suppressing cardiomyocyte pyroptosis via the NLRP3/caspase 1/GSDMD pathway - Jun Li; Da Teng; Wenjuan Jia; Lei Gong; Haibin Dong; Chunxiao Wang; Lihui Zhang; Bowen Xu; Wenlong Wang; Lin Zhong; Jianxun Wang; Jun Yang (Inflammation Research, 2024)
Objective Sepsis-induced cardiomyopathy (SICM) is a life-threatening complication. Phospholipase D2 (PLD2) is crucial in mediating inflammatory reactions and is associated with the prognosis of patients with sepsis. Whether PLD2 is involved in the pathophysiology of SICM remains unknown. This study aimed to investigate the effect of PLD2 knockout on SICM and to explore potential mechanisms. Methods The SICM model was established using cecal ligation and puncture in wild-type and PLD2-knockout mice and lipopolysaccharide (LPS)-induced H9C2 cardiomyocytes. Transfection with PLD2-shRNA lentivirus and a PLD2 overexpression plasmid were used to interfere with PLD2 expression in H9C2 cells. Cardiac pathological alterations, cardiac function, markers of myocardial injury, and inflammatory factors were used to evaluate the SICM model. The expression of pyroptosis-related proteins (NLRP3, cleaved caspase 1, and GSDMD-N) was assessed using western blotting, immunofluorescence, and immunohistochemistry. Results SICM mice had myocardial tissue damage, increased inflammatory response, and impaired heart function, accompanied by elevated PLD2 expression. PLD2 deletion improved cardiac histological changes, mitigated cTNI production, and enhanced the survival of the SICM mice. Compared with controls, PLD2-knockdown H9C2 exhibits a decrease in inflammatory markers and lactate dehydrogenase production, and scanning electron microscopy results suggest that pyroptosis may be involved. The overexpression of PLD2 increased the expression of NLRP3 in cardiomyocytes. In addition, PLD2 deletion decreased the expression of pyroptosis-related proteins in SICM mice and LPS-induced H9C2 cells. Conclusion PLD2 deletion is involved in SICM pathogenesis and is associated with the inhibition of the myocardial inflammatory response and pyroptosis through the NLRP3/caspase 1/GSDMD pathway.

Biodegradation of phthalate acid esters and whole-genome analysis of a novel Streptomyces sp. FZ201 isolated from natural habitats - Nai-Xian Feng; Da-Wei Li; Fei Zhang; Hui Bin; Yi-Tong Huang; Lei Xiang; Bai-Lin Liu; Quan-Ying Cai; Yan-Wen Li; De-Lin Xu; Yunchang Xie; Ce-Hui Mo (Journal of Hazardous Materials, 2024)

Humic substances mediated superior photochemical pollutant conversion on defective TiO2 in environmentally relevant matrices: The key roles of oxygen vacancy in surface interactions, oxidant activation and radical generation - Song Hu; Lyumeng Ye; Bing-Jie Tian; Jia-Ying Li; Ai-Yong Zhang; Lu Zhao; Chi Zhang; Chu Jiang; Zhi-Xian Lin; Wei Da; Qi-Xin Wei (Science of The Total Environment, 2024)

Identifying service bottlenecks in public bikesharing flow networks - Da Lei; Long Cheng; Pengfei Wang; Xuewu Chen; Lin Zhang (Journal of Transport Geography, 2024)

Thiosulfate/FeCl3 pre-treatment enhances short-chain fatty acid production and mitigates H2S generation during anaerobic fermentation of waste activated sludge: Performance, microbial community and ecological analyses - Boyi Cheng; Da Zhang; Qingshan Lin; Lichang Zhou; Jinqi Jiang; Xinqi Bi; Wei Jiang; Feixiang Zan; Zongping Wang; Guanghao Chen; Gang Guo (Bioresource Technology, 2024)

Inhibition of quorum sensing serves as an effective strategy to mitigate the risks of human bacterial pathogens in soil - Jinghan Zhang; Kun Lu; Lin Zhu; Na Li; Da Lin; Yangjuan Cheng; Meizhen Wang (Journal of Hazardous Materials, 2024)

Characterization of microbial contamination in agricultural soil: A public health perspective - Xiaodi Li; Lin Zhu; Si-Yu Zhang; Jingpeng Li; Da Lin; Meizhen Wang (Science of The Total Environment, 2024)

A novel method for the evaluation of ship berthing risk using AIS data - Bowen Lin; Mao Zheng; Xiumin Chu; Mingyang Zhang; Wengang Mao; Da Wu (Ocean Engineering, 2024)

Triclocarban exhibits higher adipogenic activity than triclosan through peroxisome proliferator-activated receptors pathways - Jia-Da Zhang; Sen He; Ting-Ting He; Chuan-Hai Li; Bing-Hua Yan; Yuan Yang; Jian Yang; Lin Luo; Yu-Long Yin; Lin-Ying Cao (Environmental Pollution, 2024)

Mechanical robust, adhesive, self-healable and biodegradable protein-based electronic skin sensors for smart elderly care - Ying-Ao Zhang; Chen-Yu Wang; Xiao-Xue Wang; Meng Yin; Ke Wang; Da-Wei Zhou; Hong-Long Zheng; Shou-Shan Yu; Shuang Li; Ke-Zheng Chen; Sheng-Lin Qiao (Chemical Engineering Journal, 2024)

The apple lipoxygenase MdLOX3 positively regulates zinc tolerance - Guo-Lin Chen; Da-Ru Wang; Xin Liu; Xun Wang; Hao-Feng Liu; Chun-Ling Zhang; Zhen-Lu Zhang; Lin-Guang Li; Chun-Xiang You (Journal of Hazardous Materials, 2024)

Toll-Like Receptor 4 Deficiency Ameliorates Propofol-Induced Impairments of Cognitive Function and Synaptic Plasticity in Young Mice - Qiao-Ding Dai; Kang-Song Wu; Li-Ping Xu; Yan Zhang; Na Lin; Yao Jiang; Chong-Yu Shao; Li-Da Su (Molecular Neurobiology, 2024)

Toxic vascular effects of polystyrene microplastic exposure - Jianlong Yan; Yanbin Pan; Junbo He; Xinli Pang; Wenming Shao; Caiping Wang; Rongning Wang; Yaqiong He; Min Zhang; Juheng Ye; Chaolan Lin; Feng Lin; et al. (Science of The Total Environment, 2023)

Exploring the applications of carbon dioxide radical anion in organic synthesis - Yong-Yuan Gui; Si-Shun Yan; Wei Wang; Lin Chen; Wei Zhang; Jian-Heng Ye; Da-Gang Yu (Science Bulletin, 2023)

Widespread clay authigenesis and highly congruent silicate weathering in the Marinoan aftermath - Yi-Sheng Yin; Guang-Yi Wei; Philip A.E. Pogge von Strandmann; Maxwell A. Lechte; Simon V. Hohl; Yi-Bo Lin; Da Li; Tianyu Chen; Tao Yang; Feifei Zhang; Terry T. Isson; He Zhang; et al. (Earth and Planetary Science Letters, 2023)

Pyroxenite–harzburgite sequences in the Dazhuqu ophiolite (Southern Tibet) formed through hydrous melt infiltration and melt–peridotite reaction - Zhen-Yu Zhang; Chuan-Zhou Liu; Yan Liang; Tong Liu; Chang Zhang; Bo-Da Liu; Yin-Zheng Lin; Wei-Qi Zhang; Wen-Bin Ji (Contributions to Mineralogy and Petrology, 2023)

Impacts of climate change on herpetofauna diversity in the Qinghai‐Tibetan Plateau - Alex Plimo Karuno; Xue Mi; Youhua Chen; Da‐Hu Zou; Wei Gao; Bao‐Lin Zhang; Wei Xu; Jie‐Qiong Jin; Wen‐Jing Shen; Song Huang; Wei‐Wei Zhou; Jing Che (Conservation Biology, 2023)
Although numerous studies on the impacts of climate change on biodiversity have been published, only a handful are focused on the intraspecific level or consider population‐level models (separate models per population). We endeavored to fill this knowledge gap relative to the Qinghai‐Tibetan plateau (QTP) by combining species distribution modeling (SDMs) with population genetics (i.e., population‐level models) and phylogenetic methods (i.e., phylogenetic tree reconstruction and phylogenetic diversity analyses). We applied our models to 11 endemic and widely distributed herpetofauna species inhabiting high elevations in the QTP. We aimed to determine the influence of environmental heterogeneity on species’ responses to climate change, the magnitude of climate‐change impacts on intraspecific diversity, and the relationship between species range loss and intraspecific diversity losses under 2 shared socioeconomic pathways (SSP245 and SSP585) and 3 future periods (2050s, 2070s, and 2090s). The effects of global climatic change were more pronounced at the intraspecific level (22% of haplotypes lost and 36% of populations lost) than the morphospecies level in the SSP585 climate change scenario. Maintenance of genetic diversity was in general determined by a combination of factors including range changes, species genetic structure, and the part of the range predicted to be lost. This is owing to the fact that the loss and survival of populations were observed in species irrespective of the predicted range changes (contraction or expansion). In the southeast (mountainous regions), climate change had less of an effect on range size (>100% in 3 species) than in central and northern QTP plateau regions (range size

C-doped ZnO nanocomposites molecularly imprinted photoelectrochemical sensor for ultrasensitive and selective detection of oxytetracycline in milk - Huafang Zhang; Qinghong Pan; Wanying Cai; Xiaowei Shi; Da-Peng Yang; Hetong Lin; Enhui Qiu (Food Chemistry, 2023)

Tropospheric ozone is a catastrophe, and ethylenediurea (EDU) is a phytoprotectant, recent reports on climate change scenario: A review - Sunil K. Gupta; Yang Da; Yun-Bing Zhang; Vivek Pandey; Jiao-Lin Zhang (Atmospheric Pollution Research, 2023)

The conversion of organic sulfur and strontium into inorganic compounds during the molten salt oxidation of mixed resin - Xin Liu; Yong-De Yan; Yang-Hai Zheng; Wen-Da Xu; Yun Xue; Jing-Ping Wang; Qing-Guo Zhang; Yue-Lin Wang; Fu-Qiu Ma (Journal of Environmental Chemical Engineering, 2023)

Metformin improves sheep sperm cryopreservation via vitalizing the AMPK pathway - Xing Zhang; Song-Mao Guo; Da-Wei Zhu; Yu Li; Fei Wen; Ming Xian; Zhang-Tao Hu; Qian-Long Zou; Li-Kun Zhang; Yu-Lin Chen; Jian-Hong Hu (Theriogenology, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

The effect of chlorogenic acid, a potential botanical insecticide, on gene transcription and protein expression of carboxylesterases in the armyworm (Mythimna separata) - Dong-jiang Lin; Ya-xin Zhang; Yong Fang; San-ji Gao; Ran Wang; Jin-da Wang (Pesticide Biochemistry and Physiology, 2023)

Loss of OsARF18 function confers glufosinate resistance in rice - Jin-Qiu Xia; Da-Yu He; Qin-Yu Liang; Zheng-Yi Zhang; Jie Wu; Zi-Sheng Zhang; Jing Zhang; Lin Wang; Cong-He Zhang; Ping-Xia Zhao; Cheng-Bin Xiang (Molecular Plant, 2023)

Characterization of the vertical evolution of urban nocturnal boundary layer by UAV measurements: Insights into relations to cloud radiative effect - Lin Shen; Jiaoshi Zhang; Yin Cheng; Xiaofeng Lu; Haosheng Dai; Dexia Wu; Da-Ren Chen; Jianguo Liu; Huaqiao Gui (Environmental Research, 2023)

Effect of copper ions on transformation of organic sulfur in cationic exchange resins in Li2CO3–Na2CO3–K2CO3 molten-salt system - Zhi Zhang; Yun Xue; Yue-Lin Wang; Wen-Da Xu; Yong-De Yan; Yang-Hai Zheng; Fu-Qiu Ma; Guo-Qiang Li (Chemosphere, 2023)

Industrial symbiosis promoting material exchanges in Ulan Buh Demonstration Eco-industrial Park: A multi-objective MILP model - Hao Yu; Lin Da; Yalun Li; Yanqiong Chen; Qingdan Geng; Zhibin Jia; Yun Zhang; Jinhua Li; Caixia Gao (Journal of Cleaner Production, 2023)

Recent advances in luminescence and aptamer sensors based analytical determination, adsorptive removal, degradation of the tetracycline antibiotics, an overview and outlook - Ma-Lin Cui; Zi-Xuan Lin; Qing-Fan Xie; Xiao-Yan Zhang; Bing-Qing Wang; Miao-Ling Huang; Da-Peng Yang (Food Chemistry, 2023)

Effect of Tyrosol Acyl Esters on the Antioxidant Status of Mussel ( Mytilus edulis ) Oil During Accelerated Oxidative Storage - Qian Wang; Mo-Tong Zhang; Xin-Miao Wang; Guan-Hua Zhao; Yuan-Yuan Hu; Fa-Wen Yin; Hui-Lin Liu; Xiao-Yang Liu; Da-Yong Zhou (Journal of Aquatic Food Product Technology, 2023)

Short-chain fatty acid production and phosphorous recovery from waste activated sludge via anaerobic fermentation: A comparison of in-situ and ex-situ thiosulfate-assisted Fe2+/persulfate pretreatment - Boyi Cheng; Da Zhang; Qingshan Lin; Shihao Xi; Jie Ma; Feixiang Zan; Basanta Kumar Biswal; Zongping Wang; Gang Guo (Science of The Total Environment, 2023)

Elucidating colony bloom formation mechanism of a harmful alga Phaeocystis globosa (Prymnesiophyceae) using metaproteomics - Hua-Min Cheng; Shu-Feng Zhang; Xiao-Lian Ning; Jian-Xiang Peng; Dong-Xu Li; Hao Zhang; Kun Zhang; Lin Lin; Si-Qi Liu; Walker O. Smith; Da-Zhi Wang (Science of The Total Environment, 2023)

Physiological response and photosynthetic recovery to an extreme drought: Evidence from plants in a dry-hot valley savanna of Southwest China - Da Yang; Yang-Si-Ding Wang; Qin Wang; Yan Ke; Yun-Bing Zhang; Shi-Bao Zhang; Yong-Jiang Zhang; Nate G. McDowell; Jiao-Lin Zhang (Science of The Total Environment, 2023)

Effects of low salinity stress on osmoregulation and gill transcriptome in different populations of mud crab Scylla paramamosain - Wen-Bin Xu; Yan-Mei Zhang; Bang-Ze Li; Chen-Yang Lin; Da-Yong Chen; Yuan-Xin Cheng; Xiao-Ling Guo; Wei-Ren Dong; Miao-An Shu (Science of The Total Environment, 2023)

Ultrapotassic enclaves in the Miocene adakitic granitoids, southern Tibet: Direct evidence for collision-related crust-mantle interaction and its implications - Chang-da Wu; Yuan-chuan Zheng; Bo Xu; Zeng-qian Hou; Peng Chai; Xin Li; Lin-yuan Zhang; Zi-xuan Wang; Lu Wang; Yang Shen (Lithos, 2023)

Improving the genome and proteome annotations of the marine model diatom Thalassiosira pseudonana using a proteogenomics strategy - Xiao-Huang Chen; Ming-Kun Yang; Yuan-Yuan Li; Zhang-Xian Xie; Shu-Feng Zhang; Mats Töpel; Shady A. Amin; Lin Lin; Feng Ge; Da-Zhi Wang (Marine Life Science & Technology, 2023)
Diatoms are unicellular eukaryotic phytoplankton that account for approximately 20% of global carbon fixation and 40% of marine primary productivity; thus, they are essential for global carbon biogeochemical cycling and climate. The availability of ten diatom genome sequences has facilitated evolutionary, biological and ecological research over the past decade; however, a complimentary map of the diatom proteome with direct measurements of proteins and peptides is still lacking. Here, we present a proteome map of the model marine diatom Thalassiosira pseudonana using high-resolution mass spectrometry combined with a proteogenomic strategy. In-depth proteomic profiling of three different growth phases and three nutrient-deficient samples identified 9526 proteins, accounting for ~ 81% of the predicted protein-coding genes. Proteogenomic analysis identified 1235 novel genes, 975 revised genes, 104 splice variants and 234 single amino acid variants. Furthermore, our quantitative proteomic analysis experimentally demonstrated that a considerable number of novel genes were differentially translated under different nutrient conditions. These findings substantially improve the genome annotation of T. pseudonana and provide insights into new biological functions of diatoms. This relatively comprehensive diatom proteome catalog will complement available diatom genome and transcriptome data to advance biological and ecological research of marine diatoms.

ZnO/C nanocomposite grafted molecularly imprinted polymers as photoelectrochemical sensing interface for ultrasensitive and selective detection of chloramphenicol - Huafang Zhang; Zewen Kang; Hu Zhu; Hetong Lin; Da-Peng Yang (Science of The Total Environment, 2023)

Triclocarban and triclosan exacerbate high-fat diet-induced hepatic lipid accumulation at environmental related levels: The potential roles of estrogen-related receptors pathways - Xin Li; Jia-Da Zhang; Han Xiao; Sen He; Ting-Ting He; Xiao-Min Ren; Bing-Hua Yan; Lin Luo; Yu-Long Yin; Lin-Ying Cao (Science of The Total Environment, 2023)

Stilbenes with potent cytotoxicity from the seedcases of Paeonia suffruticosa Andrews - Meng-Yue Yang; Zhao-Xiang Shao; Yue-Tong Wang; Yong-Lian Hou; Ding-Kang Zhu; Sha Chen; Ya-Hui Zhang; Fei Cao; Yong-Kui Jing; Bin Lin; Zhan-Lin Li; Da-Hong Li; et al. (Phytochemistry, 2023)

Effects of oxygen content on gaseous and solid products during molten salt oxidation of cation exchange resins - Yun Xue; Yue-Lin Wang; Yang-Hai Zheng; Yu-Sheng Yang; Wen-Da Xu; Yong-De Yan; Ran Zhao; Qing-Guo Zhang; Xin Liu; Fu-Qiu Ma; Mi-Lin Zhang (Environmental Science and Pollution Research, 2022)

Long‐term drought aggravates instability of alpine grassland productivity to extreme climatic event - Yun L. He; Jin S. Wang; Da S. Tian; Quan Quan; Lin Jiang; Fang F. Ma; Lu Yang; Fang Y. Zhang; Qing P. Zhou; Shu L. Niu (Ecology, 2022)
The frequency and severity of extreme weather events are increasing and expected to increase more in the future, together with global change. However, how extreme events and global change factors interactively influence community structures and ecosystem processes is largely unknown. Here, we investigated the responses of the temporal stability and resilience of aboveground net primary productivity (ANPP) of an alpine meadow to an extreme flooding event under different treatments of experimental drought and clipping. We found that ecosystems that were exposed to drought treatments for 3 years significantly decreased the temporal stability of community productivity but increased resilience to flooding, whereas their resistance to or recovery from flooding did not change. Neither clipping nor its interaction with drought altered the responses of these community stability metrics to flooding. Drought treatments significantly decreased plant species richness and asynchrony and dominant species stability, leading to a decrease in temporal stability and an increase in resilience in response to the extreme flooding event. The study also revealed that the change in species asynchrony was the dominant impact pathway determining the responses of resilience and temporal stability to flooding. Our results highlight that alpine grassland that experiences a multiyear drought may aggravate the instability of community productivity to extreme climatic events by reducing species asynchrony.

Metabolic tuning of a stable microbial community in the surface oligotrophic Indian Ocean revealed by integrated meta-omics - Zhang-Xian Xie; Ke-Qiang Yan; Ling-Fen Kong; Ying-Bao Gai; Tao Jin; Yan-Bin He; Ya-Yu Wang; Feng Chen; Lin Lin; Zhi-Long Lin; Hong-Kai Xu; Zong-Ze Shao; et al. (Marine Life Science & Technology, 2022)
Understanding the mechanisms, structuring microbial communities in oligotrophic ocean surface waters remains a major ecological endeavor. Functional redundancy and metabolic tuning are two mechanisms that have been proposed to shape microbial response to environmental forcing. However, little is known about their roles in the oligotrophic surface ocean due to less integrative characterization of community taxonomy and function. Here, we applied an integrated meta-omics-based approach, from genes to proteins, to investigate the microbial community of the oligotrophic northern Indian Ocean. Insignificant spatial variabilities of both genomic and proteomic compositions indicated a stable microbial community that was dominated by Prochlorococcus , Synechococcus , and SAR11. However, fine tuning of some metabolic functions that are mainly driven by salinity and temperature was observed. Intriguingly, a tuning divergence occurred between metabolic potential and activity in response to different environmental perturbations. Our results indicate that metabolic tuning is an important mechanism for sustaining the stability of microbial communities in oligotrophic oceans. In addition, integrated meta-omics provides a powerful tool to comprehensively understand microbial behavior and function in the ocean.

Dissecting the Neural Circuitry for Pain Modulation and Chronic Pain: Insights from Optogenetics - Fang Guo; Yu Du; Feng-Hui Qu; Shi-Da Lin; Zhong Chen; Shi-Hong Zhang (Neuroscience Bulletin, 2022)
Pain is an unpleasant sensory and emotional experience associated with, or resembling that associated with, actual or potential tissue damage. The processing of pain involves complicated modulation at the levels of the periphery, spinal cord, and brain. The pathogenesis of chronic pain is still not fully understood, which makes the clinical treatment challenging. Optogenetics, which combines optical and genetic technologies, can precisely intervene in the activity of specific groups of neurons and elements of the related circuits. Taking advantage of optogenetics, researchers have achieved a body of new findings that shed light on the cellular and circuit mechanisms of pain transmission, pain modulation, and chronic pain both in the periphery and the central nervous system. In this review, we summarize recent findings in pain research using optogenetic approaches and discuss their significance in understanding the pathogenesis of chronic pain.

A 40‐year climatology of summer heavy hourly rainfall over mountainous Shanxi in China - Chunqing Dong; Da‐Lin Zhang (International Journal of Climatology, 2022)
In this study, a statistical analysis of the spatiotemporal characteristics of summer heavy hourly rainfall (HHR) events during 1979–2018 over mountainous Shanxi Province is performed in order to examine regional climate change over such a transition region between North China and Northwest China. Results show that the regional 40‐year annual mean summer rainfall is about 272 mm, about 37% of which is associated with HHR events. High‐frequency and high‐intensity HHR events tend to take place in eastern mountainous subregions, whereas most basin subregions experience HHR events with low frequency and low intensity, showing the important influences of local topography and its interaction with prevailing large‐scale flows. The important topographical influences are also reflected by the observations that most mountainous subregions exhibit a major late‐afternoon peak with a secondary early morning maximum, and that the associated diurnal variations are much greater in amplitude than those in basin subregions. It is found that the regional total annual summer rainfall has a decreasing trend during the first 20 years, mostly by non‐HHR contributions, but a rapid increasing trend during the recent 20 years, with dominant HHR contributions. Most subregions with the increasing trends of HHR frequency are those dominated by rapidly increasing surface temperatures. In particular, more frequent HHR events occur over major urbanization areas, that are in close proximity to complex topography, during the recent two decades. The decadal trends in HHR are found to be correlated to the distribution and intensity changes of the East Asian summer monsoon. The above results have important implications to the operational prediction of HHR events, and a better understanding of regional climate change over mountainous Shanxi Province.

Transcriptomic analyses provide insight into adventitious root formation of Euryodendron excelsum H. T. Chang during ex vitro rooting - Yuping Xiong; Shuangyan Chen; Zhenpeng Wei; Xiaohong Chen; Beiyi Guo; Ting Zhang; Yuying Yin; Xincheng Yu; Jinhui Pang; Meiyun Niu; Xinhua Zhang; Yuan Li; et al. (Plant Cell, Tissue and Organ Culture (PCTOC), 2022)

Estimation of permafrost thermal behavior using Fourier series model - Yan-yu Zhang; Shu-ying Zang; Lin Zhao; Da-long Ma; Yue Lin; Hao Li (Journal of Mountain Science, 2022)

Distribution characteristics of per- and polyfluoroalkyl substances (PFASs) in human urines of acrylic fiber plant and chemical plant - Lin Peng; Wang Xu; Qinghuai Zeng; Yao Cheng; Yingjie Zhang; Ying Guo; Da Chen; Chao Jiang; Fei Wang (Environmental Science and Pollution Research, 2021)

On the Diurnal Cycle of Heavy Rainfall over the Sichuan Basin during 10–18 August 2020 - Rudi Xia; Yali Luo; Da-Lin Zhang; Mingxin Li; Xinghua Bao; Jisong Sun (Advances in Atmospheric Sciences, 2021)
A sustained heavy rainfall event occurred over the Sichuan basin in southwest China during 10–18 August 2020, showing pronounced diurnal rainfall variations with nighttime peak and afternoon minimum values, except on the first day. Results show that the westward extension of the anomalously strong western Pacific subtropical high was conducive to the maintenance of a southerly low-level jet (LLJ) in and to the southeast of the basin, which favored continuous water vapor transport and abnormally high precipitable water in the basin. The diurnal cycle of rainfall over the basin was closely related to the periodic oscillation of the LLJ in both wind speed and direction that was caused by the combination of inertial oscillation and terrain thermal forcing. The nocturnally enhanced rainfall was produced by moist convection mostly initiated during the evening hours over the southwest part of the basin where high convective available potential energy with moister near-surface moist air was present. The convective initiation took place as cold air from either previous precipitating clouds from the western Sichuan Plateau or a larger-scale northerly flow met a warm and humid current from the south. It was the slantwise lifting of the warm, moist airflow above the cold air, often facilitated by southwest vortices and quasi-geostrophic ascent, that released the convective instability and produced heavy rainfall.

Initiation of efficient C 4 pathway in response to low ambient CO 2 during the bloom period of a marine dinoflagellate - Hao Zhang; Youping Zhou; Tian‐Qi Liu; Xi‐Jie Yin; Lin Lin; Qiang Lin; Da‐Zhi Wang (Environmental Microbiology, 2021)
Summary Dinoflagellates are important primary producers and major causative agents of harmful algal blooms in the global ocean. Despite the great ecological significance, the photosynthetic carbon acquisition by dinoflagellates is still poorly understood. The pathways of photosynthetic carbon assimilation in a marine dinoflagellate Prorocentrum donghaiense under both in situ and laboratory‐simulated bloom conditions were investigated using a combination of metaproteomics, qPCR, stable carbon isotope and targeted metabolomics approaches. A rapid consumption of dissolved CO 2 to generate high biomass was observed as the bloom proceeded. The carbon assimilation genes and proteins including intracellular carbonic anhydrase 2, phosphoenolpyruvate carboxylase, phosphoenolpyruvate carboxykinase and RubisCO as well as their enzyme activities were all highly expressed at the low CO 2 level, indicating that C 4 photosynthetic pathway functioned in the blooming P . donghaiense cells. Furthermore, δ 13 C values and content of C 4 compound (malate) significantly increased with the decreasing CO 2 concentration. The transition from C 3 to C 4 pathway minimizes the internal CO 2 leakage and guarantees efficient carbon fixation at the low CO 2 level. This study demonstrates the existence of C 4 photosynthetic pathway in a marine dinoflagellate and reveals its important complementary role to assist carbon assimilation for cell proliferation during the bloom period.

Stoichiometric relations of C, N, and P in urban top soils in Nanjing, China, and their biogeochemical implications - Jin-Ling Yang; Da-Gang Yuan; Yu-Guo Zhao; Yue He; Gan-Lin Zhang (Journal of Soils and Sediments, 2021)

Heavy metals and health risk of rice sampled in Yangtze River Delta, China - Jian Lin; Da Sun; Ziliang Zhang; Zengqiang Duan; Jinlong Dong (Food Additives & Contaminants Part B-Surveillance, 2021)

Understanding the dynamical-microphysical-electrical processes associated with severe thunderstorms over the Beijing metropolitan region - Xiushu Qie; Shanfeng Yuan; Zhixiong Chen; Dongfang Wang; Dongxia Liu; Mengyu Sun; Zhuling Sun; Abhay Srivastava; Hongbo Zhang; Jingyu Lu; Hui Xiao; Yongheng Bi; et al. (Science China Earth Sciences, 2021)

2020 taxonomic update for phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Daniela Alioto; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Simon J. Anthony; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Tomáš Bartonička; et al. (Archives of Virology, 2020)

Interferon-α2b spray inhalation did not shorten virus shedding time of SARS-CoV-2 in hospitalized patients: a preliminary matched case-control study - Shao-rui Hao; Ren Yan; Shan-yan Zhang; Jiang-shan Lian; Huan Cai; Xiao-li Zhang; Lin Zheng; Hong-yu Jia; Jian-hua Hu; Guo-dong Yu; Jue-qing Gu; Chan-yuan Ye; et al. (Journal of Zhejiang University-SCIENCE B, 2020)

Contamination characteristics of heavy metals in particle size fractions from street dust from an industrial city, Central China - Ping Zhong; Jia-Quan Zhang; Da-Mao Xu; Qian Tian; Tian-Peng Hu; Xiang-Yi Gong; Chang-Lin Zhan; Shan Liu; Xin-Li Xing; Shi-Hua Qi (Air Quality, Atmosphere & Health, 2020)

Sideswiping Tropical Cyclones and Their Associated Precipitation over China - Tian Feng; Fumin Ren; Da-Lin Zhang; Guoping Li; Wenyu Qiu; Hui Yang (Advances in Atmospheric Sciences, 2020)

Comparison of epidemiological and clinical characteristics of COVID-19 patients with and without Wuhan exposure - Jiang-shan Lian; Huan Cai; Shao-rui Hao; Xi Jin; Xiao-li Zhang; Lin Zheng; Hong-yu Jia; Jian-hua Hu; Shan-yan Zhang; Guo-dong Yu; Jue-qing Gu; Chan-yuan Ye; et al. (Journal of Zhejiang University-SCIENCE B, 2020)

Contrasting the Pb (II) and Cd (II) tolerance of Enterobacter sp. via its cellular stress responses - Zhongquan Jiang; Liu Jiang; Lin Zhang; Mu Su; Da Tian; Tong Wang; Yalin Sun; Ying Nong; Shuijin Hu; Shimei Wang; Zhen Li (Environmental Microbiology, 2020)
Summary Successful application of microorganisms to heavy metal remediation depends on their resistance to toxic metals. This study contrasted the differences of tolerant mechanisms between Pb 2+ and Cd 2+ in Enterobacter sp. Microbial respiration and production of formic acid showed that Enterobacter sp. had a higher tolerant concentration of Pb (>1000 mg l −1 ) than Cd (about 200 mg l −1 ). Additionally, SEM confirmed that most of Pb and Cd nanoparticles (NPs) were adsorbed onto cell membrane. The Cd stress, even at low concentration (50 mg l −1 ), significantly enlarged the sizes of cells. The cellular size raised from 0.4 × 1.0 to 0.9 × 1.6 μm on average, inducing a platelet‐like shape. In contrast, Pb cations did not stimulate such enlargement even up to 1000 mg l −1 . Moreover, Cd NPs were adsorbed homogeneously by almost all the bacterial cells under TEM. However, only a few cells work as ‘hot spots’ on the sorption of Pb NPs. The heterogeneous sorption might result from a ‘self‐sacrifice’ mechanism, i.e., some cells at a special life stage contributed mostly to Pb sorption. This mechanism, together with the lower mobility of Pb cations, caused higher microbial tolerance and removal efficiency towards Pb 2+ . This study sheds evident contrasts of bacterial resistance to the two most common heavy metals.

Cadmium immobilization in aqueous solution by Aspergillus niger and geological fluorapatite - Christopher Uche Okolie; Haoming Chen; Yexin Zhao; Da Tian; Lin Zhang; Mu Su; Zhonquan Jiang; Zhen Li; Huixin Li (Environmental Science and Pollution Research, 2020)

Roles of Synoptic to Quasi-Monthly Disturbances in Generating Two Pre-Summer Heavy Rainfall Episodes over South China - Zhina Jiang; Da-Lin Zhang; Hongbo Liu (Advances in Atmospheric Sciences, 2020)

A Two-Step GRIN Lens Coating for In Vivo Brain Imaging - Yupeng Yang; Lifeng Zhang; Zhenni Wang; Bo Liang; Giovanni Barbera; Casey Moffitt; Yun Li; Da-Ting Lin (Neuroscience Bulletin, 2019)

Fluids discrimination by ray-path elastic impedance inversion: A successful case from Sulige tight gas field - Da-Xing Wang; Hao-Fan Wang; Jin-Feng Ma; Yong-Gang Wang; Na Zhang; Lin Li (Applied Geophysics, 2019)

Population pharmacokinetics of oxcarbazepine active metabolite in Chinese paediatric epilepsy patients and its application in individualised dosage regimens - Wei-wei Lin; Xi-wen Li; Zheng Jiao; Jin Zhang; Xin Rao; Da-yong Zeng; Xin-hua Lin; Chang-lian Wang (European Journal of Clinical Pharmacology, 2019)

Provenance of the Langjiexue Group to the south of the Yarlung-Tsangpo Suture Zone in southeastern Tibet: Insights on the evolution of the Neo-Tethys Ocean in the Late Triassic - Da-Ren Fang; Gen-Hou Wang; Ken-ichiro Hisada; Guo-Li Yuan; Fang-Lin Han; Dian Li; Yu Tang; Qiu-Ming Pei; Liang-Liang Zhang (International Geology Review, 2019)

A new insight into lead (II) tolerance of environmental fungi based on a study of Aspergillus niger and Penicillium oxalicum - Da Tian; Zhongquan Jiang; Liu Jiang; Mu Su; Zheye Feng; Lin Zhang; Shimei Wang; Zhen Li; Shuijin Hu (Environmental Microbiology, 2019)
Summary Environmental microorganisms have been widely applied in heavy metal remediation. This study explored the mechanisms of lead tolerance of two typical filamentous fungi, Aspergillus niger and Penicillium oxalicum . It is shown that the mechanisms of reducing Pb toxicity by these two fungi have three major pathways. The secreted oxalic acid can react with Pb (II) to form insoluble Pb minerals, primarily lead oxalate. Then, the enhanced biosorption via forming new border of cell wall prevents the transportation of Pb (II) into hypha. In addition, the fungal activity could be maintained even at high Pb concentration due to the intracellular accumulation. It was confirmed that A. niger has the higher Pb tolerance (up to 1500 mg l −1 Pb level) compared with P. oxalicum (up to 1000 mg l −1 ). Meanwhile, Pb levels below 1000 mg l −1 partially stimulate the bioactivity of A. niger , which was confirmed by its elevated respiration (from 53 to 63 mg C l −1 medium h −1 ). This subsequently enhanced microbial functions of A. niger to resist Pb toxicity. A better understanding of Pb tolerance of these two fungi sheds a bright future of applying them to remediate lead‐contaminated environments.

Contamination characteristics and potential environmental implications of heavy metals in road dusts in typical industrial and agricultural cities, southeastern Hubei Province, Central China - Da-Mao Xu; Jia-Quan Zhang; Bo Yan; Hao Liu; Li-Li Zhang; Chang-Lin Zhan; Li Zhang; Ping Zhong (Environmental Science and Pollution Research, 2018)

Impacts of Land Cover Changes on Ecosystem Carbon Stocks Over the Transboundary Tumen River Basin in Northeast Asia - Hengxing Xiang; Mingming Jia; Zongming Wang; Lin Li; Dehua Mao; Da Zhang; Guishan Cui; Weihong Zhu (Chinese Geographical Science, 2018)

Metatranscriptome analysis reveals environmental and diel regulation of a Heterosigma akashiwo (raphidophyceae) bloom - Nanjing Ji; Lingxiao Lin; Ling Li; Liying Yu; Yaqun Zhang; Hao Luo; Meizhen Li; Xinguo Shi; Da‐Zhi Wang; Senjie Lin (Environmental Microbiology, 2018)
Summary Despite numerous laboratory studies on physiologies of harmful algal bloom (HAB) species, physiologies of these algae during a natural bloom are understudied. Here, we investigated a bloom of the raphidophyte Heterosigma akashiwo in the East China Sea in 2014 using metabarcode (18S rDNA) and metatranscriptome sequencing. Based on 18S rDNA analyses, the phytoplankton community shifted from high diversity in the pre‐bloom stage to H. akashiwo predominance during the bloom. A sharp decrease in ambient dissolved inorganic phosphate and strong up‐regulation of phosphate and dissolved organic phosphorus (DOP) uptake genes, including the rarely documented (ppGpp)ase, in H. akashiwo from pre‐bloom to bloom was indicative of rapid phosphorus uptake and efficient utilization of DOP that might be a driver of the H. akashiwo bloom. Furthermore, observed up‐regulated expression of mixotrophy‐related genes suggests potential contribution of mixotrophy to the bloom. Accelerating photosynthetic carbon fixation was also implied by the up‐regulation of carbonic anhydrase genes during the bloom. Notably, we also observed a strong morning‐to‐afternoon shift in the expression of many genes. Our findings provide insights into metabolic processes likely important for H. akashiwo bloom formation, and suggest the need to consider timing of sampling in field studies on this alga.

Metaproteomics of marine viral concentrates reveals key viral populations and abundant periplasmic proteins in the oligotrophic deep chlorophyll maximum of the South China Sea - Zhang‐Xian Xie; Feng Chen; Shu‐Feng Zhang; Ming‐Hua Wang; Hao Zhang; Ling‐Fen Kong; Min‐Han Dai; Hua‐Sheng Hong; Lin Lin; Da‐Zhi Wang (Environmental Microbiology, 2018)
Summary Viral concentrates (VCs), containing bioinformative DNA and proteins, have been used to study viral diversity, viral metagenomics and virus–host interactions in natural ecosystems. Besides viruses, VCs also contain many noncellular biological components including diverse functional proteins. Here, we used a shotgun proteomic approach to characterize the proteins of VCs collected from the oligotrophic deep chlorophyll maximum (DCM) of the South China Sea. Proteins of viruses infecting picophytoplankton, that is, cyanobacteria and prasinophytes, and heterotrophic bacterioplankton, such as SAR11 and SAR116, dominated the viral proteome. Almost no proteins from RNA viruses or known gene transfer agents were detected, suggesting that they were not abundant at the sampling site. Remarkably, nonviral proteins made up about two thirds of VC proteins, including overwhelmingly abundant periplasmic transporters for nutrient acquisition and proteins for diverse cellular processes, that is, translation, energy metabolism and one carbon metabolism. Interestingly, three 56 kDa selenium‐binding proteins putatively involved in peroxide reduction from gammaproteobacteria were abundant in the VCs, suggesting active removal of peroxide compounds at DCM. Our study demonstrated that metaproteomics provides a valuable avenue to explore the diversity and structure of the viral community and also the pivotal biological functions affiliated with microbes in the natural environment.

Metaproteomics reveals major microbial players and their metabolic activities during the blooming period of a marine dinoflagellate Prorocentrum donghaiense - Dong‐Xu Li; Hao Zhang; Xiao‐Huang Chen; Zhang‐Xian Xie; Yong Zhang; Shu‐Feng Zhang; Lin Lin; Feng Chen; Da‐Zhi Wang (Environmental Microbiology, 2018)
Summary Interactions between bacteria and phytoplankton during bloom events are essential for both partners, which impacts their physiology, alters ambient chemistry and shapes ecosystem diversity. Here, we investigated the community structure and metabolic activities of free‐living bacterioplankton in different blooming phases of a dinoflagellate Prorocentrum donghaiense using a metaproteomic approach. The Fibrobacteres ‐ Chlorobi ‐ Bacteroidetes group, Rhodobacteraceae , SAR11 and SAR86 clades contributed largely to the bacterial community in the middle‐blooming phase while the Pseudoalteromonadaceae exclusively dominated in the late‐blooming phase. Transporters and membrane proteins, especially TonB‐dependent receptors were highly abundant in both blooming phases. Proteins involved in carbon metabolism, energy metabolism and stress response were frequently detected in the middle‐blooming phase while proteins participating in proteolysis and central carbon metabolism were abundant in the late‐blooming phase. Beta‐glucosidase with putative algicidal capability was identified from the Pseudoalteromonadaceae only in the late‐blooming phase, suggesting an active role of this group in lysing P . donghaiense cells. Our results indicated that diverse substrate utilization strategies and different capabilities for environmental adaptation among bacteria shaped their distinct niches in different bloom phases, and certain bacterial species from the Pseudoalteromonadaceae might be crucial for the termination of a dinoflagellate bloom.

A statistical analysis of hourly heavy rainfall events over the Beijing metropolitan region during the warm seasons of 2007–2014 - Huiqi Li; Xiaopeng Cui; Da‐Lin Zhang (International Journal of Climatology, 2017)
A statistical analysis of the spatiotemporal characteristics of hourly heavy rainfall ( HHR ) events and rainstorm days, defined as greater than 20 mm h −1 and 50 mm day −1 , respectively, is performed using observations at 5‐min intervals from 155 automated weather stations ( AWSs ) over the Beijing metropolitan region ( BMR ) during the warm seasons of 2007–2014. Results show pronounced variability in the frequencies and rainfall amounts of both HHR events and rainstorm days across the BMR of less than 150 km width from the west to east. That is, higher‐ (lower) frequency HHR events with more (less) accumulated rainfall amounts take place in eastern Haidian and over the BMR 's northeast mountains (west and northwest mountains). Many extreme rainfall and even record‐breaking events, in terms of the frequency, duration, rainfall amount and intensity, are found to occur in the regions of high‐frequency HHR events and rainstorm days. The frequency of rainstorm days with HHR events accounts for more than 50% of that of total rainstorm days over the BMR 's plains and near the northeast mountains. Results also show that HHR events occur most frequently in late July, and typically peak during 1600–2000 LST . A comparison of the averaged surface meteorological variables and upper‐air sounding at 0800 LST between HHR and non‐ HHR days reveals that the occurrences of the HHR events coincide with the distribution of surface warmer and more humid air as well as organized convergence in the presence of an unstable environment with surface south‐ to southeasterly winds, low‐level south to southwesterly flows and a deep layer of higher moisture content. These results suggest likely the positive influences of urban environment and mountain‐plain circulations on the generation of the HHR events, given favourable larger‐scale conditions.

Identification of the Genetic Cause for Childhood Disintegrative Disorder by Whole-Exome Sequencing - Zhu Wen; Tian-Lin Cheng; Da-Zhi Yin; Shi-Bang Sun; Zheng Wang; Shun-Ying Yu; Yi Zhang; Zilong Qiu; Ya-Song Du (Neuroscience Bulletin, 2017)

Celastrol, produced by Tripterygium wilfordii Hook F. enhances defense response in cucumber seedlings against diverse environmental stresses - Li-jun Zhu; Xing-guang Deng; Li-juan Zou; Peng-xu Li; Jun-qiang Wu; Da-wei Zhang; Honghui Lin (Journal of Plant Biology, 2017)

Dissipation of excess excitation energy of the needle leaves in Pinus trees during cold winters - AO Zhang; Zhen-Hai Cui; Jia-Lin Yu; Zi-Ling Hu; Rui Ding; Da-Ming Ren; Li-Jun Zhang (International Journal of Biometeorology, 2016)

Prey selection and foraging behavior of the whelk Rapana venosa - Nan Hu; Fang Wang; Tao Zhang; Hao Song; Zheng-Lin Yu; Da-Peng Liu (Marine Biology, 2016)

Ground-based radar reflectivity mosaic of mei-yu precipitation systems over the Yangtze River–Huaihe River basins - Yali Luo; Weimiao Qian; Yu Gong; Hongyan Wang; Da-Lin Zhang (Advances in Atmospheric Sciences, 2016)

Microsatellite records for volume 8, issue 3 - Yan-Ling Cao; Lívia Izabela Caputo; Hongyi Cheng; Fausto Moreira da Silva Carmo; Leiliane Campos de Carvalho; Gabriel de Menezes Yazbeck; Zélia de Oliveira Teixeira; Jiaxin Fu; José Antonio Guerrero; Guibing Hu; Jun Li; Zhihua Lin; et al. (Conservation Genetics Resources, 2016)

Ordovician intrusive rocks from the eastern Central Asian Orogenic Belt in Northeast China: chronology and implications for bidirectional subduction of the early Palaeozoic Palaeo-Asian Ocean - Hongying Li; Zhiguang Zhou; Pengju Li; Da Zhang; Changfeng Liu; XiaoQi Zhao; Lizhen Chen; Congnan Gu; Tingting Lin; Mengmeng Hu (International Geology Review, 2016)

Human amniotic epithelial stem cells promote wound healing by facilitating migration and proliferation of keratinocytes via ERK, JNK and AKT signaling pathways - Bin Zhao; Jia-Qi Liu; Zhao Zheng; Jun Zhang; Shu-Yue Wang; Shi-Chao Han; Qin Zhou; Hao Guan; Chao Li; Lin-Lin Su; Da-Hai Hu (Cell and Tissue Research, 2016)

Proanthocyanidins accelerate the germination of cucumber (Cucumis sativus L.) seeds - Li-jun Zhu; Xing-guang Deng; Li-juan Zou; Jun-qiang Wu; Da-wei Zhang; Hong-hui Lin (Journal of Plant Biology, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

α7nAChR is expressed in satellite cells at different myogenic status during skeletal muscle wound healing in rats - Zhi-Ling Tian; Shu-Kun Jiang; Miao Zhang; Meng Wang; Jiao-Yong Li; Rui Zhao; Lin-Lin Wang; Min Liu; Shan-Shan Li; Meng-Zhou Zhang; Da-Wei Guan (Journal of Molecular Histology, 2015)

Comparative proteomics reveals highly and differentially expressed proteins in field‐collected and laboratory‐cultured blooming cells of the diatom S keletonema costatum - Hao Zhang; Da‐Zhi Wang; Zhang‐Xian Xie; Shu‐Fei Zhang; Ming‐Hua Wang; Lin Lin (Environmental Microbiology, 2015)
Summary Diatoms are a major phytoplankton group causing extensive blooms in the ocean. However, little is known about the intracellular biological processes occurring during the blooming period. This study compared the protein profiles of field‐collected and laboratory‐cultured blooming cells of S keletonema costatum , and identified highly and differentially expressed proteins using the shotgun proteomic approach. A total of 1372 proteins were confidently identified with two or more peptides. Among them, 222 and 311 proteins were unique to the laboratory and field samples respectively. Proteins involved in photosynthesis, translation, nucleosome assembly, carbohydrate and energy metabolism dominated the protein profiles in both samples. However, different features of specific proteins were also found: proteins participated in light harvesting, photosynthetic pigment biosynthesis, photoprotection, cell division and redox homeostasis were highly detected in the field sample, whereas proteins involved in translation, amino acid and protein metabolic processes, and nitrogen and carbon assimilation presented high detection rates in the laboratory sample. ATP synthase cf1 subunit beta and light harvest complex protein were the most abundant protein in the laboratory and field samples respectively. These results indicated that S . costatum had evolved adaptive mechanisms to the changing environment, and integrating field and laboratory proteomic data should provide comprehensive understanding of bloom mechanisms.

Expression and Functional Analysis of a Pathogenesis-Related Protein 1 Gene, TcLr19PR1, Involved in Wheat Resistance Against Leaf Rust Fungus - Lin Gao; Shen Wang; Xiao-Ying Li; Xue-Jun Wei; Yan-Jun Zhang; Hai-Yan Wang; Da-Qun Liu (Plant Molecular Biology Reporter, 2015)

Numerical simulations of local circulation and its response to land cover changes over the Yellow Mountains of China - Die Wang; Junfeng Miao; Da-Lin Zhang (Journal of Meteorological Research, 2015)

Identification of genes involved in biosynthesis of mannan polysaccharides in Dendrobium officinale by RNA-seq analysis - Chunmei He; Jianxia Zhang; Xuncheng Liu; Songjun Zeng; Kunlin Wu; Zhenming Yu; Xiaojuan Wang; Jaime A. Teixeira da Silva; Zijian Lin; Jun Duan (Plant Molecular Biology, 2015)

Escitalopram Ameliorates Forskolin-Induced Tau Hyperphosphorylation in HEK239/tau441 Cells - Qing-Guo Ren; Yan-Juan Wang; Wei-Gang Gong; Qi-Da Zhou; Lin Xu; Zhi-Jun Zhang (Journal of Molecular Neuroscience, 2015)

Induction of plant virus defense response by brassinosteroids and brassinosteroid signaling in Arabidopsis thaliana - Da-Wei Zhang; Xing-Guang Deng; Fa-Qiong Fu; Hong-Hui Lin (Planta, 2015)

Association of novelty-related behaviors and intravenous cocaine self-administration in Diversity Outbred mice - Price E. Dickson; Juliet Ndukum; Troy Wilcox; James Clark; Brittany Roy; Lifeng Zhang; Yun Li; Da-Ting Lin; Elissa J. Chesler (Psychopharmacology, 2015)

Ambient noise spectral properties in the north area of Xisha - Lianglong Da; Chao Wang; Mei Han; Lin Zhang (Acta Oceanologica Sinica, 2014)

Retraction Note to: Characterization of cancer stem-like cells in the side population cells of human gastric cancer cell line MKN-45 - Hai-hong Zhang; Ai-zhen Cai; Xue-ming Wei; Li Ding; Feng-zhi Li; Ai-ming Zheng; Da-jiang Dai; Rong-rong Huang; Hou-jun Cao; Hai-yang Zhou; Jian-mei Wang; Xue-jing Wang; et al. (Journal of Zhejiang University-SCIENCE B, 2014)

Editorial - Yihui Ding; Guoxiong Wu; Da-Lin Zhang; Renhe Zhang (Journal of Meteorological Research, 2014)

Complete genome sequence analysis identifies a new genotype of brassica yellows virus that infects cabbage and radish in China - Xiao-Yan Zhang; Hai-Ying Xiang; Cui-Ji Zhou; Da-Wei Li; Jia-Lin Yu; Cheng-Gui Han (Archives of Virology, 2014)

The Transurethral Seminal Vesiculoscopy in the Diagnosis and Treatment of the Seminal Vesicle Disease - Cong-hui Han; Qing Liang; Bing-zheng Dong; Lin Hao; Tao Fan; Jun-jie Zhang; Wen-da Zhang; Bo Chen; Xiang-zheng Qiu; Xiang-ju Zhou; Chang-song Pei (Cell Biochemistry and Biophysics, 2013)

High prevalence of torque teno sus virus in China and genetic diversity of the 5’ non-coding region - Shao-Lun Zhai; Jin-Xue Long; Wen-Kang Wei; Qin-Ling Chen; Man-Lin Luo; Dian-Hong Lv; Da-Cheng Wu; Fei Gao; Shi-Shan Yuan; Guang-Zhi Tong; Zu-Zhang Wei (Archives of Virology, 2013)

Impact of manure application on forms and quantities of phosphorus in a Chinese Cambisol under different land use - Qiao Yun Xue; Imran Haider Shamsi; Da Sheng Sun; Anne Ostermann; Qi Chun Zhang; Yong Song Zhang; Xian Yong Lin (Journal of Soils and Sediments, 2013)

RETRACTED ARTICLE: Characterization of cancer stem-like cells in the side population cells of human gastric cancer cell line MKN-45 - Hai-hong Zhang; Ai-zhen Cai; Xue-ming Wei; Li Ding; Feng-zhi Li; Ai-ming Zheng; Da-jiang Dai; Rong-rong Huang; Hou-jun Cao; Hai-yang Zhou; Jian-mei Wang; Xue-jing Wang; et al. (Journal of Zhejiang University-SCIENCE B, 2013)

Alpha-momorcharin, a RIP produced by bitter melon, enhances defense response in tobacco plants against diverse plant viruses and shows antifungal activity in vitro - Feng Zhu; Ping Zhang; Yan-Fa Meng; Fei Xu; Da-Wei Zhang; Jian Cheng; Hong-Hui Lin; De-Hui Xi (Planta, 2013)

Evaluation of landslide risk based on synchronization of nonlinear motions in observed data - Da-Chao Lin; Jing-Luo Cai; Zhang-Lin Guo; Fan-Lei Zeng; Feng-Ping An; Hai-Bo Liu (Natural Hazards, 2013)

Prediction of tropical cyclone frequency with a wavelet neural network model incorporating natural orthogonal expansion and combined weights - Hexiang Liu; Da-Lin Zhang; Jianwei Chen; Qingjuan Xu (Natural Hazards, 2013)

Comparative study of four rice cultivars with different levels of cadmium tolerance - Xiao Wang; Zhong-Wei Zhang; Shi-Hua Tu; Wen-Qiang Feng; Fei Xu; Feng Zhu; Da-Wei Zhang; Jun-Bo Du; Shu Yuan; Hong-Hui Lin (Biologia, 2013)

XPA A23G polymorphism and susceptibility to cancer: a meta-analysis - Jun Liu; Zhen Zhang; Xiao-Lin Cao; Da-Peng Lei; Zhong-Qiu Wang; Tong Jin; Xin-Liang Pan (Molecular Biology Reports, 2012)

Production of cloned transgenic cow expressing omega-3 fatty acids - Xia Wu; Hongsheng Ouyang; Biao Duan; Daxin Pang; Li Zhang; Ting Yuan; Lian Xue; Daibang Ni; Lei Cheng; Shuhua Dong; Zhuying Wei; Lin Li; et al. (Transgenic Research, 2012)

Differential DNA Methylation Status Between Human Preadipocytes and Mature Adipocytes - Jin-gai Zhu; Li Xia; Chen-bo Ji; Chun-mei Zhang; Guan-zhong Zhu; Chun-mei Shi; Lin Chen; Da-ni Qin; Xi-rong Guo (Cell Biochemistry and Biophysics, 2012)

Functional analysis of Waardenburg syndrome-associated PAX3 and SOX10 mutations: report of a dominant-negative SOX10 mutation in Waardenburg syndrome type II - Hua Zhang; Hongsheng Chen; Hunjin Luo; Jing An; Lin Sun; Lingyun Mei; Chufeng He; Lu Jiang; Wen Jiang; Kun Xia; Jia-Da Li; Yong Feng (Human Genetics, 2012)

Is the isentropic surface always impermeable to the potential vorticity substance? - Chanh Q. Kieu; Da-Lin Zhang (Advances in Atmospheric Sciences, 2012)

Seasonal variation in population characteristics and management implications for brown rats (Rattus norvegicus) within their native range in Harbin, China - Da-Wei Wang; Lin Cong; Ling-Fen Yue; Bao-Huan Huang; Jian-Xu Zhang; Yu Wang; Ning Li; Xiao-Hui Liu (Journal of Pest Science, 2011)

Retinol, vitamins A, C, and E and breast cancer risk: a meta-analysis and meta-regression - Hu Fulan; Jiang Changxing; Wang Yi Baina; Zhang Wencui; Lin Chunqing; Wang Fan; Li Dandan; Sun Dianjun; Wang Tong; Pang Da; Zhao Yashuang (Cancer Causes & Control, 2011)

Characteristics of CO2 release from forest soil in the mountains near Beijing - Xiang Yang Sun; Cheng Da Gao; Lin Zhang; Su Yan Li; Yong Qiao (Environmental Monitoring and Assessment, 2011)

Nicotine dependence and serum BDNF levels in male patients with schizophrenia - Xiang Yang Zhang; Mei Hong Xiu; Da Chun Chen; Fu De Yang; Gui Ying Wu; Lin Lu; Therese A. Kosten; Thomas R. Kosten (Psychopharmacology, 2010)

Molecular characterization of two Chinese isolates of Beet western yellows virus infecting sugar beet - Hai-Ying Xiang; Shu-Wei Dong; Hui-Zhong Zhang; Wei-Lin Wang; Min-Quan Li; Cheng-Gui Han; Da-Wei Li; Jia-Lin Yu (Virus Genes, 2010)

Up-regulation of Orai1 in murine allergic rhinitis - Lin Lin; Chunquan Zheng; Luping Zhang; Cuidi Da; Keqing Zhao (Histochemistry and Cell Biology, 2010)

Growth hormone and two forms of insulin-like growth factors I in the giant grouper (Epinephelus lanceolatus): molecular cloning and characterization of tissue distribution - Haiyan Dong; Lingxian Zeng; Da Duan; Haifa Zhang; Yunxin Wang; Wensheng Li; Haoran Lin (Fish Physiology and Biochemistry, 2010)

Morphologic observation and classification criteria of atretic follicles in guinea pigs - Wei Wang; Hong-lin Liu; Wei Tian; Fen-fen Zhang; Yan Gong; Jin-wei Chen; Da-gan Mao; Fang-xiong Shi (Journal of Zhejiang University-SCIENCE B, 2010)

Mesoscale barotropic instability of vortex Rossby waves in tropical cyclones - Wei Zhong; Han-Cheng Lu; Da-Lin Zhang (Advances in Atmospheric Sciences, 2010)

Superoxide dismutase and cytokines in chronic patients with schizophrenia: association with psychopathology and response to antipsychotics - Xiang Yang Zhang; Dong Feng Zhou; Ling Yan Qi; Song Chen; Lian Yuan Cao; Da Chun Chen; Mei Hong Xiu; Fan Wang; Gui Ying Wu; Lin Lu; Therese A. Kosten; Thomas R. Kosten (Psychopharmacology, 2009)

Potential ecological risk of cadmium, lead and arsenic in agricultural black soil in Jilin Province, China - Hui-cong Cao; Zhao-qing Luan; Jin-da Wang; Xue-lin Zhang (Stochastic Environmental Research and Risk Assessment, 2009)

Demographic trade‐offs in a neutral model explain death‐rate–abundance‐rank relationship - Kui Lin; Da-Yong Zhang; Fangliang He (Ecology, 2009)
The neutral theory of biodiversity has been criticized for its neglect of species differences. Yet it is much less heeded that S. P. Hubbell's definition of neutrality allows species to differ in their birth and death rates as long as they have an equal per capita fitness. Using the lottery model of competition we find that fitness equalization through birth–death trade‐offs can make species coexist longer than expected for demographically identical species, whereas the probability of monodominance for a species under zero‐sum neutral dynamics is equal to its initial relative abundance. Furthermore, if newly arising species in a community survive preferentially they are more likely to slip through the quagmire of rareness, thus creating a strong selective bias favoring their community membership. On the other hand, high‐mortality species, once having gained a footing in the community, are more likely to become abundant due to their compensatory high birth rates. This unexpected result explains why a positive association between species abundance and per capita death rate can be seen in tropical‐forest communities. An explicit incorporation of interspecific trade‐offs between birth and death into the neutral theory increases the theory's realism as well as its predictive power.

Lower serum cytokine levels in smokers than nonsmokers with chronic schizophrenia on long-term treatment with antipsychotics - Xiang Yang Zhang; Lian Yuan Cao; Cai Song; Gui Ying Wu; Da Chun Chen; Ling Yan Qi; Fan Wang; Mei Hong Xiu; Song Chen; Yingyang Zhang; Lin Lu; Therese A. Kosten; et al. (Psychopharmacology, 2008)

Ischemic preconditioning induces chaperone hsp70 expression and inhibits protein aggregation in the CA1 neurons of rats - Peng-Fei Ge; Tian-Fei Luo; Ji-Zhou Zhang; Da-Wei Chen; Yong-Xin Luan; Shuang-Lin Fu (Neuroscience Bulletin, 2008)

Glutathione S-transferases M1 and T1 polymorphisms and arsenic content in hair and urine in two ethnic clans exposed to indoor combustion of high arsenic coal in Southwest Guizhou, China - Guo-fang Lin; Hui Du; Ji-gang Chen; Hong-chao Lu; Jin-xiang Kai; Yun-shu Zhou; Wei-chao Guo; Xin-jiang Zhang; Da-ru Lu; Klaus Golka; Jian-hua Shen (Archives of Toxicology, 2007)

Genotypic Analysis of Multidrug-Resistant Mycobacterium tuberculosis Isolates Recovered From Central China - Shu-Lin Zhang; Hua Qi; Dun-Lian Qiu; Da-Xu Li; Jie Zhang; Chang-Mei Du; Guo-Bin Wang; Zhi-Rong Yang; Qun Sun (Biochemical Genetics, 2007)

Distribution of lead in urban soil and its potential risk in Shenyang City, China - Jin-da Wang; Hui-min Ren; Jing-shuang Liu; Jun-bao Yu; Xue-lin Zhang (Chinese Geographical Science, 2006)

Pollen phenolics and regulation of pollen foraging in honeybee colony - Fang-Lin Liu; Xue-Wen Zhang; Jian-Ping Chai; Da-Rong Yang (Behavioral Ecology and Sociobiology, 2006)

The impact of the storm-induced SST cooling on hurricane intensity - Tong Zhu; Da-Lin Zhang (Advances in Atmospheric Sciences, 2006)

Sensitivity of cyclone tracks to the initial moisture distribution: A moist potential vorticity perspective - Zuohao Cao; Da-Lin Zhang (Advances in Atmospheric Sciences, 2005)

Mapping QTLs of traits contributing to yield and analysis of genetic effects in tetraploid cotton - Dao-Hua He; Zhong-Xu Lin; Xian-Long Zhang; Yi-Chun Nie; Xiao-Ping Guo; Chun-Da Feng; James McD. Stewart (Euphytica, 2005)

Tracking surface cyclones with moist potential vorticity - Zuohao Cao; Da-Lin Zhang (Advances in Atmospheric Sciences, 2004)

Coexistence of cryptic species - Da‐Yong Zhang; Kui Lin; Ilkka Hanski (Ecology Letters, 2004)
Recent discovery of cryptic species in fig‐pollinating wasps creates a puzzle for the ecological competition theory: how do two or more apparently identical species coexist? Conventional theory predicts that they should not. Chesson (Trends Ecol. Evol., 1991, 6 , 26–28) identified one exception which he considered unlikely to occur in reality: coexistence might be possible if appropriate social behaviour was discriminately directed towards conspecifics and heterospecifics. Here we present an example of the exception by showing that two identical species with local mate competition and population size‐dependent sex ratio adjustment may coexist. The new findings about fig‐pollinating wasps provide a putative example of unexpected coexistence of identical competitors via this mechanism.

Role of tumor metastasis suppressor gene KAI1 in digestive tract carcinomas and cancer cells - Qiao Wu; Yuan Ji; Ming-qing Zhang; Yu-qiang Chen; Fu Chen; Da-lin Shi; Zong-hui Zheng; Yao-jian Huang; Wen-jin Su (Cell and Tissue Research, 2003)

Strand Compositional Asymmetries of Nuclear DNA in Eukaryotes - Deng K. Niu; Kui Lin; Da-Yong Zhang (Journal of Molecular Evolution, 2003)

Dependence of Hurricane intensity and structures on vertical resolution and time-step size - Da-Lin Zhang; Xiaoxue Wang (Advances in Atmospheric Sciences, 2003)

Spatial-temporal variation of heavy metal elements content in covering soil of reclamation area in fushun coal mine - Jun-bao Yu; Jing-shuang Liu; Jin-da Wang; Zhong-gen Li; Xue-lin Zhang (Chinese Geographical Science, 2002)

A personal perspective on the further reform of the advances in atmospheric sciences - Da-Lin Zhang (Advances in Atmospheric Sciences, 2002)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)